Effect of edaphic fertilization on the growth and development of Phaseolus vulgaris cv. ICA Cerinza - Bautista-Zamora, Daniel; Chavarro-Rodríguez, Carmen; Cáceres-Zambrano, Jeimmy; Buitrago-Mora, Sebastián (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
Crop nutrition is a central axis in agricultural production; however, sometimes fertilizer additions do not correspond to the edaphic conditions of the area of cultivation or the requirements of the plants; this inadequate fertilization management induces soil degradation, decreased yield and high production costs. An alternative to soil conservation is the application of organic amendments, which increase the availability of nutrients and give rise to the recovery of soils. The aim of this study was to determine the effect on the growth and development of Phaseolus vulgaris var. Cerinza with the application of organic amendments (compost and vermicompost) and commercial fertilizer. Plant height, photosynthetic pigment content, number of leaves and reproductive structures, fresh and dry weight, leaf area, area under the canopy and growth indexes: specific leaf area (SLA), crop growth rate (CGR) and net assimilation rate (NAR) were evaluated. The results at 56 days after sowing showed significant differences in height, where the treatments of compost and vermicompost had higher values in relation to the commercial fertilization. In the other growth variables, there were no significant differences between the treatments.